The Impact of Gender on Learning Anxiety and English Communication Willingness among Chinese University Athletes: A Sports Psychology Analysis - Guojun Tan; Chia-Ching Tu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigated the influence of gender disparities and English learning apprehension on the inclination of Chinese university athletes to engage in English communication. Employing purposive sampling, 787 athletes from diverse universities in China were selected as participants. An online questionnaire survey encompassed the administration of the Learning Anxiety Scale and the Scale of ability to converse in English. Scale validation ensued through confirmatory factor analysis, while the mediation effect of the structural model, along with gender differentials in path coefficients, was scrutinized using structural equation modelling (SEM). Outcomes unveiled the noteworthy impact of gender disparities on the conversational proficiency in English and learning anxiety among Chinese university athletes. Particularly, female athletes exhibited elevated levels of English learning apprehension compared to their male counterparts, thus signifying the necessity for supplementary support and resources to bolster their confidence in English communication. These findings accentuate the significance of athletes' perceptions regarding English acquisition and their attitudes toward English communication in moulding their conversational proficiency. The study carries significant implications for the realms of sports psychology and language education, underscoring the imperative to address gender disparities and attitudes toward English learning within language education initiatives tailored for athletes.